Evaluation of diabetic neuropathy: correlation between cutaneous sensibility in the feet, clinical and eletroneuromyographic findings - Souza, Ary; Nery, Caio Augusto de Souza; Marciano, Lúcia Helena Soares Camargo; Garbino, José Antonio (Acta Fisiátrica, 2005)
Objective: To evaluate the efficacy of the Semmes-Weinstein monofilaments for diagnosis and prognosis of feet with diabetic neuropathy. Methods: a prospective study with 35 type II diabetic patients. Patients took part of a protocol including anamnesis, complaints, physical examination, electrophysiological study and determination of cutaneous sensitivity of the feet. Results: Semmes-Weinstein monofilaments and electrophysiological study coincided highly. The Semmes-Weinstein monofilaments were sensitive to detect patients with some degree of change. Discussion: A good degree of agreement was observed between the Semmes-Weinstein monofilaments and electrophysiological study methods, as expressed by the correlation coefficient of Spearman (r= 0.677). The Semmes-Weinstein monofilaments were more sensitive to detect patients with some type of change, because we observed 91% of patients between grade 2 and grade 5. The electrophysiological study detected 69% of patients in the same range. Major difference was observed in patients without involvement (grade 1) showing elevated sensitivity of the Semmes-Weinstein monofilaments. The study also showed good correlation between clinical involvement of patients with neurological deficits measured with the Semmes-Weinstein monofilaments. Conclusion: the Semmes-Weinstein monofilaments are reliable to diagnose neurophatic diabetes of the feet. There is correlation between neurological findings and clinical criteria obtained with the monofilaments. The Semmes-Weinstein monofilaments are helpful in the evaluation of prognosis and evolution of the diabetic foot and they may be safely utilized in the evaluation of the feet with peripheral neuropathy.